Does Computed Tomography Have the Ability to Differentiate Aggressive From Nonaggressive Solid Pseudopapillary Neoplasm?. Issue 3 (May 2018) - Rastogi, Ashita; Assing, Mathew; Taggart, Mellisa; Rao, Brinda; Sun, Jia; Elsayes, Khaled; Tamm, Eric; Bhosale, Priya
Abstract : Objective: The aim of the study was to assess the ability of contrast-enhanced computed tomography (CECT) to differentiate aggressive from nonaggressive solid pseudopapillary neoplasms (SPNs). Materials and Methods: Forty treatment-naive patients with pathologically proven pancreatic SPNs were included. Imaging characteristics were determined by consensus of 3 radiologists blinded to histopathologic aggressiveness. All patients underwent 4-phase CECT using a pancreatic protocol. The regions of interest of the tumor and the normal pancreas were documented on all phases. Lymph nodes were considered metastatic if greater than 1.0 cm in short-axis diameter. Fisher exact and Wilcoxon rank-sum tests were used to compare between aggressive and nonaggressive tumors. Results: No significant difference was noted between imaging covariates, such as internal hemorrhage, calcification, wall thickness perceptibility, vascular invasion, margins, cystic component, and pancreatic and biliary ductal dilation. Tumors with greater than 62.5 Hounsfield units and progressive enhancement during the delayed phase had aggressive characteristics ( P = 0.03). Conclusions: On delayed phase CECT, pathologically aggressive SPNs may show greater enhancement than nonaggressive SPNs. Abstract : Supplemental digital content is available in the text.